PERBANDINGAN EFEKTIVITAS EKSTRAK ETANOL DAUN AFRIKA (VERNONIA AMYGDALINA DEL.) DENGAN SIMVASTATIN TERHADAP KADAR HDL PADA TIKUS JANTAN GALUR WISTAR YANG DIINDUKSI KUNING TELUR - YUFI YUWARDITRA; ISRA THRISTY (JURNAL ILMIAH SIMANTEK, 2021)
Egg yolk is a food that contains a lot of lipids so that it can cause dyslipidemia which is characterized by a decrease in HighDensity Lipoprotein (HDL). In overcoming this, simvastatin are often used therapies. Indonesian people are starting to worryabout the side effects of treatment using chemicals. Using many traditional medicinal herbs. One type of plant used is Africanleaves (Vernonia amygdalina Del.). To study the interaction of African leaf ethanol extract (Vernonia amygdalina Del.) withsimvastatin on HDL levels in wistar strain male rats induced by egg yolk. This study was an experimental study with thePosttest method with a control group design. This study uses test animals male white rats Wistar (Rattus novergicus) whichwill be divided into 5 groups and using Oneway ANOVA test data analysis. From the results of data analysis, the averagevalue of HDL extract of African leaf ethanol obtained was 72.6; simvastatin 75,8 and a combination of ethanol extract ofAfrican leaves with simvastatin 81,6. Oneway ANOVA analysis showed (p <0.05). Giving ethanol extract of African leaves,simvastatin and Combination of extracts Ethanol leaves of Africa with simvastatin did not differ in increasing HDL levels ofmice.